2019
DOI: 10.3889/oamjms.2019.357
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of MMR Proteins with Clinicopathological Correlation in Colorectal Cancer in Egypt

Abstract: BACKGROUND: Microsatellite instability (MSI) is the genetic pathway underlying 15% of sporadic colorectal carcinoma (CRC) and hereditary non-polyposis CRC. MSI-H CRC has a distinct clinicopathological characteristic including excess mucin and signet ring component, proximal colon, Crohn’s like reaction, lymphocytic infiltration, and better survival. AIM: This research aims to screen Egyptian CRC patients for MSI status by IHC testing of expression of the MMR proteins in correlation to its clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 35 publications
4
11
1
Order By: Relevance
“…Previous study comparing Egyptian CRC patients with Western CRC patients, found that the frequency of MSI-H tumors in the Egyptian group was higher than that in the Western sporadic group (37% vs. 13%, p = 0.002) (Soliman et al, 2001). Soliman et al, (2019) found that the expression level of MSI-H was 47.0%, which was more than 10% higher than the present results. However, many Egyptian studies on MSI prevalence in CRC patients showed that it was higher than that reported from western population, yet there was no clear explanation for this difference.…”
Section: Msi and Relation To Patient Characteristics And Life-stylecontrasting
confidence: 75%
“…Previous study comparing Egyptian CRC patients with Western CRC patients, found that the frequency of MSI-H tumors in the Egyptian group was higher than that in the Western sporadic group (37% vs. 13%, p = 0.002) (Soliman et al, 2001). Soliman et al, (2019) found that the expression level of MSI-H was 47.0%, which was more than 10% higher than the present results. However, many Egyptian studies on MSI prevalence in CRC patients showed that it was higher than that reported from western population, yet there was no clear explanation for this difference.…”
Section: Msi and Relation To Patient Characteristics And Life-stylecontrasting
confidence: 75%
“…However, MSI-H CRCs have been reported to demonstrate a more frequent association with proximal tumor location, poorly differentiated, mucin-containing histology, and advanced staging [23]. Another study revealed that proximal location (right side) was selected as predictors of MS-H CRC with p = 0.005 [24]. In our study, only three patients had a mass in the rectum, and they all had MS-H CRC and wild KRAS.…”
Section: Discussionmentioning
confidence: 48%
“…The low tumor cell viability was also demonstrated on gastric [ 37 ], lung cancer [ 49 ], esophagus [ 34 ], lymphoma [ 29 ], leukemia [ 27 ], ovarian cancer [ 28 ], breast cancer [ 48 , 50 ], cervical cancer [ 43 ], skin cancers [ 20 , 31 ]. Accordantly, the peptide effects on CRC cells have already been demonstrated [ 38 - 40 , 51 ].…”
Section: Discussionmentioning
confidence: 81%
“…Specifically, about metastases, melittin showed activity for lung [ 49 , 50 ], liver [ 28 , 51 ], and esophageal metastasis [ 34 ]. For bone CRC metastases, the present data are unprecedented.…”
Section: Discussionmentioning
confidence: 99%